Development and characterization of electrochemical sensors based on PAMAM dendrimers and citrate-stabilized gold nanoparticles - Tavares, Gina Marta Ferraz (2020)
Electrochemical sensors are devices that allow the detection and quantification of a certain compound in a determined sample. Nanomaterials are extremely appealing for sensing purposes due their properties. Poly(amidoamine) dendrimers and gold nanoparticles are largely explored because of their small dimensions; the latter is used for its electrocatalytic properties, whilst the former is used in biosensors for its potential as an immobilization platform for biological recognition elements. This project focused on the use of PAMAM dendrimers and gold nanoparticles in electrode modification and the assessment of these modifications. Firstly, gold and glassy carbon electrodes were sequentially modified with thiols, gold layer, G5 PAMAM-NH2 dendrimers and citrate-stabilized gold nanoparticles. The modifications were monitored by cyclic voltammetry and impedance spectroscopy in a hexacyanoferrate (II)/(III) redox couple system. All modifications were successful, with the exception of citrate-stabilized gold nanoparticle, PAMAM dendrimer and mercaptopropionic sulfonic acid modified glassy carbon electrode. In a second part, the electrocatalytic activity of the modified electrodes towards 4-nitrophenol reduction in 0.05 M phosphate buffer solution was assessed by cyclic voltammetry. G5 PAMAM NH2 dendrimer assembly over vitreous carbon-based surfaces translated to electrodes with higher sensitivity, for lower limits of detection are obtained. The lowest limit of detection was calculated for PAMAM dendrimer and 3mercaptopropionic acid-modified glassy carbon electrode, 17 M, with 4-nitrophenol in linear range of 690 – 37 M. Gold substrates proved to have poor electrocatalytic activity towards 4-nitrophenol reduction owing to the simultaneous reduction of 4-nitrophenol and solution on gold surface. As for vitreous carbon substrates, the use of gold, either as a layer or as citrate-stabilized nanoparticles, resulted in less sensitive electrodes, as suggested by higher detection limits.